2019
DOI: 10.1109/jstsp.2019.2894059
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid NOMA/OMA With Buffer-Aided Relay Selection in Cooperative Networks

Abstract: Non-orthogonal multiple access (NOMA) aims to increase the spectral efficiency of fifth generation (5G) networks by relaxing the orthogonal use of radio-resources. In this work, a network with multiple half-duplex (HD) buffer-aided (BA) relays is considered, where the source transmits with fixed rate towards two users. The users might demand the same rate by the source (e.g., two cellular users requiring the same service), or they could have different rate requirements (e.g., a cellular user coexisting with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 54 publications
0
56
0
Order By: Relevance
“…In downlink NOMA networks with a single source, multiple BA relays and two destinations, hybrid BA-NOMA/OMA was proposed in [31], integrating broadcasting in the {S→R} link and exploiting BSI in the {R→D} NOMA transmission. The steps of BA-NOMA/OMA are given in the following paragraphs:…”
Section: Ba-noma/oma: Flexible Multiple Access With Optimal Power Allmentioning
confidence: 99%
See 3 more Smart Citations
“…In downlink NOMA networks with a single source, multiple BA relays and two destinations, hybrid BA-NOMA/OMA was proposed in [31], integrating broadcasting in the {S→R} link and exploiting BSI in the {R→D} NOMA transmission. The steps of BA-NOMA/OMA are given in the following paragraphs:…”
Section: Ba-noma/oma: Flexible Multiple Access With Optimal Power Allmentioning
confidence: 99%
“…There are different methods of determining the power allocation coefficient α k in NOMA networks. In this work, power allocation follows the method that was developed in [31] which considered a two-hop relay network with two destinations with possibly heterogeneous rate requirements, as it is the case of coexisting IoT devices and users. Since a similar {R→D} link setting is studied here, readers are referred to that work for more details on calculating α k .…”
Section: Transmission In the {R→d} Linkmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that a diversity gain equal to two can be achieved for buffer sizes larger than two. Finally, Nomikos et al in [17] developed BA-ORS algorithms integrating broadcasting in the {S→R} link and combining NOMA with OMA for robustness against outages, increasing the average sum-rate and reducing the delay. Furthermore, Nomikos et al in [7] combined HD and FD BA relays with the objective of minimizing the power expenditure.…”
Section: Introductionmentioning
confidence: 99%